The therapeutic effect of modified Huangqi Guizhi Wuwu Tang for multiple myeloma: An 18-year follow-up case report. Issue 49 (December 2017) - Tian, Mingmin; Huang, Huang
Abstract: Rationale: Multiple myeloma (MM) is a hematologic malignancy characterized by proliferation of clonal plasma cells in the bone marrow. The median survival has increased to 6 years in recent years. But MM remains incurable. Some studies about the effects of Chinese herb medicine on MM have been carried out. Long survival in MM patients through Traditional Chinese Medicine (TCM) therapies has been reported rarely before. Patient concerns: We report a case of a female patient who was diagnosed with MM in 2000 at the age of 49. She received 9 cycles of multiple chemotherapeutic regimens mainly based on melphalan from September 2000 to May 2001. Though her condition was under control in some degree, she discontinued treatment due to significant side effects such as fatigue, hyperhidrosis, fever, chill, larynx mucosa ulcers, pharynx mucosa ulcers, and poor appetite. Instead, she sought treatment with TCM alone. Diagnoses: Based on the TCM theory, the patient's condition was categorized as Xue Bi. Interventions: Up to the present, the patient has been using modified Huangqi Guizhi Wuwu Tang (HGWT) continuously for 18 years. In this prescription, Radix Astragali is an important herb. When the patient's condition worsened, its dosage was increased from 30 to 120g. Besides, she has been eating Radix Astragali porridge or drinking Radix Astragali tea for almost 18 years at the same time. Outcomes: Throughout the period, no obvious side effects have been observed and her health condition remains stable. Lessons: Polysaccharides isolated from Astragalus membranaceus (Radix Astragali) and Polyporus umbellatus could promote maturation of dendritic cells. Polysaccharides and flavonoids isolated from Astragalus membranaceus could regulate bone marrow microenvironment by inhibiting secretion of interleukin (IL)-6, IL-12 p40 and bidirectionally regulating the osteogenic capacity of osteoblasts. Besides, Rhizoma Atractylodis Macrocephalae, another important component of the prescription, has inhibitory effects on osteolytic bone lesions. This case suggests TCM treatment may have a positive therapeutic effect on MM. Modified HGWT, especially the Chinese herb medicine Radix Astragali could potentially be an alternative option for the treatment of MM. Both pharmacological studies and randomized clinical trials are needed in the future. Abstract : Supplemental Digital Content is available in the text